Doing Act Of Kindness To Enhance Subjective Happiness: Correlates Of Academic Success - E. Roldan, Amalia; B. Pastrana, Nimfa (CV. Inara, 2022)
The purpose of this study is to determine the effectiveness of doing act of kindness as intervention program to enhance subjective happiness as correlates of student’s academic success for college freshmen. The subjective happiness of the respondents were assessed twice before and after the intervention program. The respondents’ academic achievement in their Psychology class was correlated to their academic achievement. Using the One – Group Pre-test and Post-test design the effectiveness of the intervention program was determined. The results of the pre-assessment (degree of their subjective happiness before the intervention program) and post-assessment (degree of their subjective happiness after the intervention program) was compared and analyzed using the t-test for dependent means. The study concluded that the respondents’ perceived degree of subjective happiness had increased after the conduct of the intervention program. The difference on the subjective happiness of the respondents before and after the intervention program is significant. Thus the intervention program is effective. There is significant relationship between the respondents’ subjective happiness and academic achievement in Psychology class. Results depict that happiness is a correlates of students’ academic success